Taming heterogenity and complexity of embedded control - Lamnabhi-Lagarrigue, F. (Françoise), 1953- (ISTE USA, 2007)
This book gathers together a selection of papers presented at the Joint CTS-HYCON Workshop on Nonlinear and Hybrid Control held at the Paris Sorbonne, France 10-12 July 2006. The main objective of the Workshop was to promote the exchange of ideas and experiences and reinforce scientific contacts in the large multidisciplinary area of the control of nonlinear and hybrid systems.